STRATEGI PEMBERDAYAAN MASYARAKAT MIS KIN DI KABUPATEN KUANTAN SINGINGI - Zaili Rusli (Universitas Riau, 2008)
One of the purpose of area autonomy is to quicken development of area throughprogram the destructing of poorness. But the problem of poverty in this time is still identically withlimitation of society to access in development. This research aim to know program strategyemeroment poor society in Kabupaten Kuantan Sengingi. Do program strategy emeroment poorsociety have given to access which enough wide in development. Population is poor societyfamily head which have child ofbalita, school age ofbase, and continuation school of. Intake ofsampel use technique of proposional sampling according to chosen countryside. Technics ofcollecting data by interview with responder and key informan. Data analysis have the character ofdescriptive is qualitative supported by data of secunder. Result of research indicate that strategyemeroment poor society with approach of economics not yet given satisfying result for the destructingof poverty of cause problems of poverty not merely economic poverty but also socialpoverty or structural poverty.